2022
DOI: 10.1007/s12282-022-01405-6
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of pelvic floor training to treat urinary incontinence in women with breast cancer: a telehealth intervention trial

Abstract: Purpose To investigate the feasibility of recruiting into a pelvic floor muscle training (PFMT) program delivered via telehealth to treat urinary incontinence (UI) in women with breast cancer on aromatase inhibitors. Methods We conducted a pre-post single cohort clinical trial with 54 women with breast cancer. Participants underwent a 12-week PFMT program using an intra-vaginal pressure biofeedback device: femfit®. The intervention included eight supervise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The feasibility of pelvic floor training through video call for women with BC has also been studied, showing significantly positive results in terms of reduction of urinary incontinence post intervention. In a study by Colombage et al [ 43 ], using an intra-vaginal pressure biofeedback device, patients learned via video call how to use train their pelvic muscles and how to use the biofeedback device. They were also virtually supervised by a physiotherapist through the 12 weeks course of the study [ 43 ].…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…The feasibility of pelvic floor training through video call for women with BC has also been studied, showing significantly positive results in terms of reduction of urinary incontinence post intervention. In a study by Colombage et al [ 43 ], using an intra-vaginal pressure biofeedback device, patients learned via video call how to use train their pelvic muscles and how to use the biofeedback device. They were also virtually supervised by a physiotherapist through the 12 weeks course of the study [ 43 ].…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%
“…In a study by Colombage et al [ 43 ], using an intra-vaginal pressure biofeedback device, patients learned via video call how to use train their pelvic muscles and how to use the biofeedback device. They were also virtually supervised by a physiotherapist through the 12 weeks course of the study [ 43 ]. The study also reports that 81% of the participants had problems when using the intra-vaginal device alone and therefore, it was only used under supervision [ 43 ].…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no studies have investigated telehealth-delivered PFMT to treat UI/FI after gynaecological cancer treatment without a clinical assessment. One study investigated the feasibility of telehealth-delivered PFMT to treat stress UI in women with breast cancer and found that it may be feasible and potentially beneficial [ 15 ]. However, we do not know if similar results will be observed in women with gynaecological cancer due to differences in demographics, and clinical and treatment characteristics between breast and gynaecological cancer survivors.…”
Section: Introductionmentioning
confidence: 99%